Corpo-Palavra - Bressan, Olívia Scarpari (2016)
I write. I rewrite. I try one, two, three, numerous times. The pen resists in continuing to give narrative a body. It falls, fainted. I keep quiet, and I keep quiet again. The medusas are multiplying, but my-yours shouts are deaf. Why so much silence? The present essay is about a creative process while writing an autofictional narrative of feminine authorship and is also about a cathartic process, a settlement of accounts with literary creation: writing as a way of saving from neurosis and also as a challenge of language construct. During the path, however, how is it possible to deal with self-censorship and with language restrictions? As Sartre says in his memoir The Words, renouncing to write it is also renouncing to ourselves. That way, in order not to renounce, I face autofictional narrative as a form of expressing my memories and my experiences: creating a double, a persona, enables me to expose myself, since autofiction doesn’t have a commitment with truth – it is a fiction that inspires itself and plays freely with biographical aspects. Thus, using the nuances offered by autofiction was the creative alternative that enabled me to write, to fable and to find a way of creative freedom in a favorable environment for it: the Creative Writing postgraduate program of Pontifícia Universidade Católica do Rio Grande do Sul.